IMPACT OF THE TRANSFER OF RICE FIELDS ON RICE PRODUCTION IN THE FRAMEWORK OF FOOD SECURITY (CASE STUDY IN KUDUS REGENCY ) - Agung Slamet Sukardi (Jurnal REP (Riset Ekonomi Pembangunan), 2022)
The conversion of rice fields in Kudus Regency has increased from year to year. Based on quantitative data, it is stated that land conversion is influenced by changes in economic structure, improvements in infrastructure facilities and population growth. In fact, the area of paddy fields has an effect on increasing total rice production, while the area of paddy fields that have been converted to non-rice fields has not been able to prove a decrease in total rice production in Kudus Regency if it is supported by agricultural technology and also agricultural intensification. Related to the fulfillment of the needs of the population of Kudus Regency for rice which is still lacking, so it needs to get serious attention from the Regional Government of Kudus Regency so that these basic needs can be fulfilled